Addressing postgraduate students’ attitudes towards research, research self-efficacy and knowledge of research in an online module - van der Westhuizen, Sanet (South African Journal of Higher Education, 2018)
The purpose of this study was to determine the degree to which an online module influenced honours students’ attitude towards research, research self-efficacy and knowledge of research. An availability sample (N= 279) of postgraduate students enrolled for an online course in research methodology (n = 97 for semester 1 in 2012 and n = 182 for semester 2 in 2012) was used. The attitude towards research scale, self-developed research self-efficacy and knowledge test was administered in a single group pre-test post-test design. Dependent t-tests revealed that in general, students’ positive attitude towards research, their research self-efficacy and knowledge of research increased from the onset to the completion of the module. However, students’ perception of the usefulness of research for their careers declined and their research anxiety and self-efficacy with regard to data analysis remained unchanged on completion of the module. These findings indicate that addressing students’ perception of the usefulness of research for their careers and their research anxiety may be more complex than anticipated and that it could be a process that is independent of addressing students’ research self-efficacy and their knowledge of research.